Motivations, Achievements, and Challenges of Self-Directed Informal Learners in Open Educational Environments and MOOCs - Curtis J. Bonk; Mimi Miyoung Lee (Journal of Learning for Development, 2017)
This research targeted the learning preferences, goals and motivations, achievements, challenges, and possibilities for life change of self-directed online learners enrolled in a massive open online course (MOOC) related to online teaching hosted by Blackboard using CourseSites. Data collection included a 40-item survey of which 159 MOOC respondents completed the close-ended survey items and 49 completed the 15 open-ended survey items. Across the data, it is clear that self-directed online learners are internally motivated and appreciate the freedom to learn and choice that open educational resources provide. People were also motivated to learn informally from personal curiosity and interest as well as professional growth needs and goals for self-improvement. Identity as a learner was positively impacted by informal online learning pursuits. Foreign language skills as well as global, cultural, historical, environmental, and health-related information were among the most desired by the survey respondents. The main obstacles to informal online learning were time, costs associated with technology use, difficulty of use, and lack of quality. Qualitative results, embedded in the findings, indicate that self-directed learners take great pleasure in knowing that they do not have to rely on others for their learning needs. Implications for instructional designers are offered.